X-Ray window simulation; the use of COMSOL 3.4 Multiphysics software (Global Journal of Science Frontier Research, 1969)
Ways are sought after, to prevent overlying target material on membrane from breaking or melting, by simulating structures (using COMSOL 3.4 Multiphysics software) of various materials. Results of these simulations and graphs (using Origin 7.5 software) are presented. The implications conferred by these graphs on the report are discussed. Power densities, of impinging electrons, thermal conductivities and thickness of membrane are considered as key parameters for optimal performance.